ABUSE OF POWER AND RESISTANCE IN SELECTED POST-COLONIAL SUB-SAHARA AFRICAN NOVELS (2014)
ABSTRACT Abuse of power, an excessive use of authority in governance or homes; and resistance, the attempt to confront such abuses, have occupied a prominent position in socio-political discourses in African literature. Existing studies on sub-Sahara African novels written from the late 1980s have focused on thematic concerns such as gender issues, disillusionments and exploitation, without giving adequate attention to the issue of abuse of power and resistance. This study, therefore, examined the forms of abuse of public and domestic power, and forms of resistance to the abuses in the selected novels, with a view to establishing the features of the abuse of power and resistance. The study adopted subalternism, a variant of postcolonial theory which articulates the lopsided relationship between the oppressor and the oppressed, and the strategies deployed by the latter to counter the excesses of the former. Five sub-Sahara African novels were selected based on their thematic affinity, relevance and period of study. The novels are Tiyambe Zeleza‟s Smouldering Charcoal (South Africa); Moses Isegawa‟s Snakepit (East Africa); Chimamanda Ngozi Adichie‟s Purple Hibiscus, Amma Darko‟s Beyond the Horizon and Jude Dibia‟s Unbridled from West Africa where abuse of power and resistance is more prominent among novelists. The data were subjected to literary analysis. Two forms of abuse of power were identified: public and domestic. Public abuse of power is manifested in democratic and military tyranny. Domestic power abuse is demonstrated through benevolent dictatorship, physical and sexual violence. Four forms of resistance were identified: activism, dissent and exile, strategic operations, and strategic confrontations. Public abuse of power in South Africa is manifested in democratic tyranny in Smouldering Charcoal. The government uses „Youth Militia Group‟ to unleash terror on those who failed to obtain party cards, and unjustly arrests and detains unsuspecting citizens. This is resisted by the victims through political and trade union activism. In East Africa, Snakepit depicts military tyranny as General Bazooka uses his position to oppress the citizens, an act resisted by some members of the military through dissent, while others in the civil society go into exile. In West Africa, Purple Hibiscus dwells on domestic power abuse revealed through benevolent dictatorship in the home. The family head, though a generous man, brutalises members of his family. The victims resist through silence and poisoning him to death. While Beyond the Horizon captures domestic abuse of power in a Ghanaian family, as women are physically abused and raped, and they resist through secret service operations; Unbridled portrays abuse of power in terms of beatings, harassments and sexual abuses in the home. The victim resists through violent confrontations, and runs away. Abuse of power, with differing manifestations, such as tyranny, dictatorship, physical and sexual abuses occur in civil, military and home contexts; and resistance through activisms, dissent, strategic operations and violent physical confrontations in post-colonial sub-Sahara African novels. Key words: Post-colonial abuse of power and resistance, sub-Sahara African novels, Public power, Domestic power, Word count: 469